STUDY ON THE PREVALENCE AND UNDERLYING FACTORS OF MYOPIA AMONG THE STUDENTS OF A MEDICAL COLLEGE IN KERALA - Shiny George and Biju Baby Joseph
Background: Few decades earlier, wearing spectacles was a province of adults over 40 years of age. Now we see more children and adolescents with spectacles/contact lenses. Various studies in Asian population show a dramatic increase in refractive error, especially myopia among school and college students. More advanced levels of education like medical education that involves extensive near work such as reading and writing have been repeatedly associated with greater myopia prevalence Objective: To study the prevalence and the underlying factors of myopia in MBBS students of a Medical college in Kerala. Research methodology: One hundred and sixty two MBBS students (2009 - 2012 batches) were examined. 40 students were selected from each class by systematic random sampling technique, their visual acuity was checked using Snellen’s Chart and Diopters were obtained. Details of factors were obtained using a questionnaire. Results: Prevalence of myopia was observed as 39.5%. First and second year students had a greater percentage of myopia with 40% & 52.5% respectively. 40.6% of myopics had positive family history of myopia (p = 0.003). Duration of TV watching and computer use showed a significant relation with myopia. (p = 0. 033, 0.009). Reading hours, type of light used, playing or texting with cell phone and sleeping habits of students were not significant. Conclusion: Prevalence of myopia was high among medical students (39.5%). Significance of genetic predisposition was well appreciated in our study.